Epidemiology of Facial Bone Fractures During the Coronavirus Disease 2019 Pandemic: A Single Korean Level I Trauma Center Study - Min Ji Kim; Kyung Min Yang; Hyoseob Lim (Journal of Trauma and Injury)
Purpose The medical community has been heavily impacted by the coronavirus disease 2019 pandemic. The management of facial trauma patients has been affected by the patient capacity of emergency rooms. In this study, we share our experiences of facial trauma management during the social lockdown period and investigate the epidemiological changes in facial bone fractures. Methods A total of 997 patients who presented to Ajou University Hospital Emergency Center and were evaluated by plastic or maxillofacial surgeons for facial trauma were included in this retrospective study. Our study design was a comparative study of two groups: the 2019 group (control) and the 2020 group (the experimental group that experienced social lockdown). Results The total number of emergency room inpatients reflected the national pandemic trends with three peaks in patient numbers. According to these trends, facial bone fractures had two different low points in August 2020 and December 2020. A comparison of the 2019 and 2020 facial bone fractures did not show a statistically significant difference in the total number of patients. An analysis of the causes of trauma showed that domestic accidents increased in 2020 (30.92%; p<0.001). Among the anatomical sites of facial injury in surgical patients, the frontozygomatic complex fracture increased the most in 2020 (p=0.018). Facial injuries with two separate sites of injury or with three or more involved sites also showed a significant increase in 2020 (p<0.001). Conclusions We demonstrated that the incidence of facial trauma patients correlated with the incidence of patients presenting to the emergency department and that facial trauma is inextricably related to multi-trauma cases. Domestic accidents and facial trauma with multiple anatomically involved sites are increasing trends that need more attention.